Kualitas Pelayanan Pencegahan dan Penanganan Kasus Kekerasan Terhadap Perempuan dan Anak di Kabupaten Cilacap - Sukma Ageng Tiara Bintang; Dyah Retna Puspita; Bambang Tri Harsanto (Asosiasi Ilmuwan Administrasi Negara (AsIAN), 2025)
Cilacap Regency is one of the areas with the highest number of violent cases in Central Java. From 2016 to 2019, there have been 465 cases of violence experienced by women and children. Of the total number of cases, 72 percent of cases were dominated by cases of violence against children. These problems, if left unchecked, will trigger various physical and psychological impacts on victims, which are feared to cause new problems. The purpose of this study is to describe the quality of services for preventing and handling cases of violence against women and children in Cilacap Regency and to analyze the inhibiting and supporting factors of the quality of services for preventing and handling cases of violence against women and children in Cilacap Regency. The research method used in this research is qualitative. The results of this study show the quality of services for handling cases of violence against women and children in Cilacap Regency can be said to be quite good. However, violence prevention services cannot be said to be good because of the five indicators measured, there are three indicators that are not yet good, namely tangibles, reliability, and assurance. Meanwhile, those who already have good service quality are shown by indicators of responsiveness and empathy. Then the supporting factors found are awareness and the rules factors. The inhibiting factors found are organizational and abilities also skills factors.